PENGARUH KONSENTRASI STRUKTUR PASAR TERHADAP KINERJA INDUSTRI KOMERSIAL PERBANKAN DI INDONESIA PERIODE TAHUN 2007 - 2011 - Mr Rofanov (Quantitative Economics Journal, 2013)
Based on the ratio of market share of 11 commercial banks discovered the phenomenon gap of the period 2007-2011 where 11 commercial banks dominate the banking market predominantly in Indonesia, including four state-owned banks. This phenomenon has resulted in the banking market structure tends to form an oligopoly, it is obviously affecting the behavior of banks that have a dominant position to maintain supernormal profit, which is reluctant to extend credit with low interest tribes and not a reflection of efficient behavior that ultimately lead to the real sector can not run role in the economy because of factors hampered financing. And with the market conditions are 11 commercial banks were so dominant, which is feared if one bank's collapse could affect the performance of banks in a systemic and even disrupt the Indonesian economy in general. The objectives of this research to determine the form of the banking market structure and analize the influence of concentration market structure and Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Net Interest Margin (NIM), and Loan to Deposit Ratio (LDR) to Return on Asset (ROA) wich is as a proxy of Financial Performance Banking in 2007 until 2011 periods. The data in this study was collected from Indonesian Banking Directory of 2007-2011. The collected sample was 11 biggest commercial banks over the period from 2007-2011. The analysis model  was used to determine the shape of banking market structure by using CR4 concentration ratio (Four Concentration Ratio) on a share of the assets, the share of third-party funding (DPK) and the share of loans, that produce banking that shaped the oligopoly market structure moderate low or concentration oligopoly level IV, where four largest banks a dominate about 42% - 50% market share. The estimation of the Fixed Effect Model unknown  that concentration market, market share, Capital Adequacy Ratio (CAR), Net Interest Margin (NIM) and the Loan to Deposit Ratio (LDR) has a positive effect on profitability (Return on Assets ) as a proxy for the performance of the banking industry. And for the  Non Performing Loan (NPL) has a negatively effect on profitability (Return on Assets) as a proxy for the performance of the banking industry.